Valorant Game Virtual Communication With Discord - Muhammad Ngizzuddin Alfaruqi; Prihatin Dwihantoro (UIN Salatiga, 2022)
Communication that occurs in the current era is progressing rapidly. The progress of communication is still at a stage that can be renewed. The development in the field of communication that occurs in the current era is caused by various capabilities and potential communication technologies so that humans can relate and meet communication needs. This study raises questions about the communication patterns that occur when playing Valorant games using discord applications. The goal of the study was to find out the communication patterns that occur in teams while playing Valorant games using Discord apps. From the results of the study, it can be concluded that, as a team game, it is necessary to organize the squad to fill certain roles. The role in the team when playing Valorant is given and becomes a specialization depending on the skills possessed. There are 2 roles in the Valorant game, namely, primary roles and secondary roles. The results also reveal that good communication in the Valorant game is important because good communication can lead to victory. Virtual communication using the Discord application is one of the things that can be used when playing Valorant games because Discord has provided space to communicate both orally and in writing. This is because when playing the Valorant game, there is no miscommunication between players in a team and they can achieve a win together.